Costs of work-related musculoskeletal disorders (MSDs) in developing countries : Colombia case (2006)
ABSTRACT: The real burden of occupational diseases, specifically work-related musculoskeletal disorders (MSDs), and its impact on workers’ productivity is not known. The situation is critical in developing countries where only cases that cause workers’ disability are recorded. In this study, the incidence of MSDs in Colombia was estimated by using the age and gender specific double incidence rate of repetitive strain injuries diseases in Finland for 2002. The results showed that the estimated number of MSDs recorded in Colombia during 2005 was 23,477 cases at the rate of 11.6 cases per 10,000 workers. The estimated total cost of these MSD cases relative to workers’ productivity was US $171.7 million, representing around 0.2% of Colombia’s Gross Domestic Product for 2005. The systematic appraisal of the incidence of MSDs and their associated cost on workers’ productivity are necessary in developing countries to reduce the costly impact on productivity and to increase workers’ well-being.